HAMSTRING/QUADRICEPS RATIO IN ACL INJURY PREDICTION IN ELITE FOOTBALL PLAYERS. Issue 4 (1st February 2017) - Grygorowicz, Monika; Michalowska, Martyna; Walczak, Tomasz; Grabski, Jakub; Pyda, Andrzej; Piontek, Tomasz
Abstract : Background: Hamstring/quadriceps conventional ratio (H/Q) has been widely used in the prediction of anterior cruciate ligament (ACL) injury; however there is still no consensus on the values that are really predictive for ACL injury in elite male football players. Objective: To verify the value of H/Q predictive for ACL injury in elite male footballers. Design: Retrospective study, analysing ACL injury occurrence in footballers and H/Q value from isokinetic tests. Setting: Male football elite division. Patients (or Participants): Records of 74 professional male footballers who played at least one season between 2010–2016 have been analysed. Interventions (or Assessment of Risk Factors): All players were monitored and treated by one clinic, thus medical history of each player was documented. ACL injury was confirmed in USG examination. Players were dichotomously categorized as injured or uninjured for data analysis. The same clinic was responsible for conducting isokinetic assessment using Biodex System 3 Pro. Retrospective footballer's records were reviewed between May 2006 and April 2016. Receiver operating characteristic (ROC) curves were used to evaluate the possibility of using the H/Q value to predict ACL injury. Level of significance was set at p<0.05 and Statistica v.12.5 software was used. Main Outcome Measurements: Area under the curve (AUC); number of ACL injuries and values of H/Q were also analysed. Results: Total 331 knee isokinetic tests of 74 elite male football players were reviewed, and data of 8 ACL injuries were analysed. Cut-off value of H/Q ratio was calculated at 0.63±0.11. The ROC analyses showed an area under the curve of 0.67 (95% CI 0.49–0.84; p=0.0598). Conclusions: Although it occurred to be insignificant we observed a tendency towards H/Q values at 0.63±0.11, that may be useful in future studies in multifactorial analysis of ACL injury prediction. However, studies on bigger sample should be performed to verify these results.